AB0903 Behcet's Disease in The Midwest Region of Ireland: Patient Access and Response To Anti-TNF Biologics. (15th July 2016) - Adeeb, F.; Ng, W.L.; Stack, A.; Fraser, A.D.
Abstract : Background: Current literature shows promising data for efficacy of anti-tumor necrosis factor (anti-TNF) biological therapy in Behcet's disease (BD) patients. Objectives: The aim was to investigate a cohort of BD patients in Midwest Region of Ireland, current prescription practice for anti TNF biologics in this cohort, patient response & the risk of serious infections or other serious side effects. Methods: All BD patients attending our rheumatology service & satisfying the ISGBD or ICBD criteria were included in the study. Response was evaluated on patient's new/worsening clinical features & improvement/resolution of clinical symptoms. Management was benchmarked against current European League Against Rheumatism (EULAR) guidelines published in 2009. Serious infection was defined as the requirement for intravenous antimicrobial therapy and hospitalization. Results: From a cohort of 22 patients, 18 (81.9%) received anti-TNF (6 males, 12 females) with mean age 38.9 years. 14 patients (77.8%) achieved complete remission & 4 patients (22.2%) achieved low disease activity on anti-TNF. Among this 3 patients (16.7%) were successfully switched to a different agent due to secondary failure, 6 patients (33.3%) needed 3 different anti-TNFs and one patient required a fourth anti-TNF therapy to achieve remission. Indications to start anti-TNF among our cohort include severe mucocutaneous lesions with significant impact to quality of life (15/18), ocular manifestations (7/18), destructive laryngeal disease (5/18), vascular manifestations (3/18) & resistance or intolerance to conventional treatments (8/18). Anti-TNF was extremely effective in suppressing the mucocutaneous oral & laryngeal manifestations, significantly improving patient's quality of life. However resistant genital ulcers was often a difficult symptom to control with 3 patients achieving partial remission.5 allergic reactions were encountered, all with administration of infliximab. 5 serious infections were documented involving 3 patients (16.7%) and all in patients aged 50 years or above. No other serious side effects were noted. Conclusions: Anti TNF-α biological therapy is an important alternative option for first line therapy in severe BD as many conventional treatments failed to maintain clinical remission and prevention of life-threatening complications. Response rates to anti-TNF-α therapy were excellent and treatment was well tolerated but should be used with caution in patients age 50 or above. BD patients who fail one anti TNF-α due to intolerance, ineffectiveness or secondary failure may still benefit from switching to another drug from this group or even re-trial of a previously administered anti-TNF. References: P.P. Sfikakis, N. Marcomichelakis, E. Alpsoy et al. Anti-TNF therapy in the management of Behçet's disease-review and basis for recommendations. Rheumatology (Oxford), 46 (2007), pp. 736–741 Hatemi G, Silman A, Bang D et al. Management of Behçet disease: a systematic literature review for the European League Against Rheumatism evidence-based recommendations for the management of Behçet disease. Ann Rheum Dis 68(10): 1528–1534 Fitzgerald CW, Adeeb F, Timon CV, Shine NP, Fraser AD, Hughes JP. Significant laryngeal destruction in a northern European cohort of Behçet's disease patients. Clin Exp Rheumatol. 2015 Nov-Dec;33(6 Suppl 94):S123–8. Disclosure of Interest: None declared